Effect of Body Weight on Reproductive Fitness in Spodoptera Litura (Lepidoptera: Noctuidae) - Xu, Jin; Chen, Peng; Li, Yong-He (International Research Journal of Insect Sciences, 2018)
The exact nature and even existence of the balance between natural and sexual selection are still controversial. Body size is a key determinant of an organism’s ecological and physiological properties. It is widely accepted that selection for higher fecundity is the main force behind the selection for larger body size. However, there are conflicting selection pressures operating on body size of both sexes in many organisms, for instance, natural selection for higher survival might reduce body size. In the present study, we found that in the common cutworm moth, Spodoptera litura, female fecundity and fertility significantly increased with her body weight, while male body weight or female–male weight interaction had no effect on female reproductive output. Results of this study also showed that heavier parents have heavier male and female offspring than those from lighter parents. Although not statistically significant, offspring from heavy and light parents showed lower survival rate than those from average weight parents.